2014
DOI: 10.1002/cyto.a.22488
|View full text |Cite
|
Sign up to set email alerts
|

Study of gemcitabine‐sensitive/resistant cancer cells by cell cloning and synchrotron FTIR microspectroscopy

Abstract: Over the last few years, significant scientific insight on the effects of chemotherapy drugs at cellular level using synchrotron-based FTIR (S-FTIR) microspectroscopy has been obtained. The work carried out so far has identified spectral differences in cancer cells before and after the addition of drugs. However, this had to account for the following issues. First, chemotherapy agents cause both chemical and morphological changes in cells, the latter being responsible for changes in the spectral profile not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
1
17
1
Order By: Relevance
“…Subtle differences in cell spectra have been used to distinguish cells in different stages in the cell cycle [2], apoptotic cells [3] or cell lines [4,5], to identify cancer cells [6], and to predict the aggressiveness of cancer cells [7]. Several studies have shown a relationship between the mode of action of chemotherapy drugs and changes in FTIR spectra of dried cells [8][9][10], as well as differences in FTIR spectra of drug-resistant and drug-sensitive cells [11][12][13]. In these studies cells were treated with a mildly cytotoxic or cytostatic concentration of drug, generally the IC 50 value for the drug toxicity, and were then collected and dried prior FTIR analysis, as water causes a strong interference in FTIR analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Subtle differences in cell spectra have been used to distinguish cells in different stages in the cell cycle [2], apoptotic cells [3] or cell lines [4,5], to identify cancer cells [6], and to predict the aggressiveness of cancer cells [7]. Several studies have shown a relationship between the mode of action of chemotherapy drugs and changes in FTIR spectra of dried cells [8][9][10], as well as differences in FTIR spectra of drug-resistant and drug-sensitive cells [11][12][13]. In these studies cells were treated with a mildly cytotoxic or cytostatic concentration of drug, generally the IC 50 value for the drug toxicity, and were then collected and dried prior FTIR analysis, as water causes a strong interference in FTIR analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular resistance pathways were specifically targeted by Yosef et al who used Raman spectral imaging to investigate the oncogenic mutation resistance to epidermal growth factor receptor targeting therapy and colon cancer cells with and without oncogenic mutations such as KRAS and BRAF mutations were treated with erlotinib, an inhibitor of epidermal growth factor receptor, in order to detect the impact of these mutations on Raman spectra of the cells as markers of cell resistance. Rutter et al utilised a cell cloning technique to specifically isolate sensitive and resistant cells from a mixed cell population, and investigated the difference in response of gemcitabine‐sensitive and gemcitabine‐resistant Calu‐1 epidermoid lung cancer cells to the commercial drug, using IR spectroscopy. Furthermore, Siddique et al showed that it was also possible to identify differences of nilotinib‐sensitive and nilotinib‐resistant K562 (a chronic myelogenous leukaemia cell line) cloned cells, using both FTIR and Raman microspectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…Rutter et al [69] investigated the difference in response of gemcitabinesensitive and gemcitabine-resistant CALU-1 epidermoid lung cancer cells to gemcitabine. By cloning sensitive and resistant cell populations, from a mixed population, they showed that PCA did not discriminate treated from untreated resistant cells, but did for sensitive cells.…”
Section: Infrared Spectroscopy For Monitoring Drug-cell Interactionmentioning
confidence: 99%